Solve the equation by factoring #17

Algebra
Tutor: None Selected Time limit: 1 Day

Solve the equation by factoring.


   -6x - 2 = (3x + 1)2


Mar 3rd, 2015

On the LHS, -6x-2=-2(3x+1), and on the RHS, it is (3x+1)^2. So common term is (3x+1). 

by factoring 3x+1, you can get (3x+1)^2+2(3x+1)=0

                                                    (3x+1)(3x+1+2)=0

                                                    (3x+1)(3x+3)=0

therefore, x=-1/3 or x=-1

Mar 3rd, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Mar 3rd, 2015
...
Mar 3rd, 2015
Dec 6th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer